Transition of care in stroke patients discharged home: a single-center prospective cohort study - M. J. de Mooij; I. Ahayoun; J. Leferink; M. J. Kooij; F. Karapinar-Çarkit; R. M. Van den Berg-Vos (BMC, 2021)
Abstract Introduction Approximately two-thirds of the patients admitted to the hospital with an ischemic stroke are discharged directly home. Discontinuity of care may result in avoidable patient harm, re-admissions and even death. We hypothesized that the transfer of information is most essential in this patient group since any future care for these patients relies solely on the information that is available to the care provider responsible at that time. Aim The objective of this study was to evaluate the continuity of transmural care in ischemic stroke patients by assessing 1) the transfer of clinical information through discharge letters to general practitioners (GPs), 2) subsequent documentation of this information and early follow-up by GPs and 3) the documentation of medication-related information in discharge letters, at GPs and community pharmacies (CPs). Methods This prospective cohort study was conducted from September 2019 through March 2020 in OLVG, Amsterdam, the Netherlands, in patients with a first stroke discharged directly home. Outcome measures were derived from national guidelines and regional agreements. Results were analyzed using descriptive analysis. Results A total of 33 patients were included. Discharge letters (n = 33) and outpatient clinic letters (n = 24) to GPs contained most of the essential items, but 16% (n = 9) of the letters were sent in time. GPs (n = 31) infrequently adhered to guidelines since 10% (n = 3) of the diagnoses were registered using the correct code and 55% (n = 17) of the patients received follow-up shortly after discharge. Medication overviews were inaccurately communicated to GPs since 62% (n = 150) of all prescriptions (n = 243) were correctly noted in the discharge letter. Further loss of information was seen as only 39% (n = 95) of all prescriptions were documented correctly in GP overviews. We found that 59% (n = 144) of the prescriptions were documented correctly in CP overviews. Conclusion In this study, we found that discontinuity of care occurred to a varying extent throughout transmural care in patients with a first stroke who were discharged home.